1970
DOI: 10.1104/pp.46.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Absence of Developing Grain on Carbohydrate Content and Senescence of Maize Leaves

Abstract: In maize (Zea mays L.) grown under normal conditions in Rhodesia, prevention of pollination or removal of the ears after flowering caused premature senescence of the leaves above the ear, preceded by the appearance of a purplish red color. In plants from which the ears had been removed the concentration of sugars and starch increased markedly in both upper and lower leaves, the increase being greater in the upper leaves.The removal of flowers or of developing fruits has been observed to delay senescence in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 7 publications
(7 reference statements)
3
35
0
Order By: Relevance
“…ear removal) results in an acceleration of leaf and plant senescence, relative to eared control plants (1,3,4,5). Crafts-Brandner et al (4) found when visual symptoms of leaf senescence were apparent, rates of accumulation of dry matter (net photosynthesis), reduced N (nitrate assimilation) and P by the shoot decreased rapidly after ear removal and ceased by 30 d after anthesis.…”
mentioning
confidence: 99%
“…ear removal) results in an acceleration of leaf and plant senescence, relative to eared control plants (1,3,4,5). Crafts-Brandner et al (4) found when visual symptoms of leaf senescence were apparent, rates of accumulation of dry matter (net photosynthesis), reduced N (nitrate assimilation) and P by the shoot decreased rapidly after ear removal and ceased by 30 d after anthesis.…”
mentioning
confidence: 99%
“…All defoliation treatments decreased the percent TNC of both stalk positions by 10 to 20 days after treatment. (Daynard et al, 1969;Hume and Campbell, 1973 Grain weight of control plants (Table 5) Concurrent with earlier senescence of leaves for most genotypes in 1979 was an increase in the days to physiological maturity and the grain Plants without ears exhibited a purple discoloration along the midrib and leaf margins similar to observations by Moss (1962) and Allison and Weinmann (1970). There was less purple discoloration with ear removal plus 50 percent defoliation than with ear removal and no defoliation.…”
Section: Resultssupporting
confidence: 54%
“…Leaf export of assimilates Hartt, 1965) has been shown to decrease, whereas leaf sugar (Sayre et al, 1931;Allison and Weinmann, 1970;Hume and Campbell, 1973;Ciha and Brun, 1978) and leaf starch (Kollman et al, 1974) have been shown to Increase following sink reduction or removal.…”
Section: Introduction I7 Materials and Methods I9mentioning
confidence: 99%
“…High N has reduced phosphate uptake in maize in a pre vious study (Bennett et al, 1962); (2) poor sink development and feedback of assimilates. Where sink development was pre vented in maize, leaf CER has decreased due to feedback of assimilates and leaf margin purpling was reported (Allison and Weinmann, 1970;Moss, 1962). The high CER cultivars in this study have been observed to tiller profusely in field experiments (Part I above) but tillers were absent from these pot-grown plants.…”
Section: Photosynthesismentioning
confidence: 70%